CORRELATION BETWEEN EXCLUSIVE BREASTFEEDING IN GROUP OF EARLY INITIATION OF BREASTFEEDING ON THE DURATION OF LACTATIONAL AMENORRHEA - Febrianto, Edison; Prabantoro, Benedictus TR; Pangemanan, Lisa (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Based on data from